2020
DOI: 10.3390/ma13184095
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Deterioration of Concrete under Dry–Wet Cycle and Sulfate Attack

Abstract: In order to study the deterioration and mechanism of dry–wet cycles and sulfate attack on the performance of concrete in seaside and saline areas, the deterioration of compressive strength of concrete with different water cement ratios under different erosion environments (sodium sulfate soaking at room temperature and coupling of dry–wet cycling and sodium sulfate) was studied here. At the same time, ICT (industrial computed tomography) and NMR (nuclear magnetic resonance) techniques were used to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…However, due to the high sulfate concentration in the water sample detection of the test tunnel, the experiment requires a strict sulfate concentration. Therefore, sodium sulfate immersion concentrations of 2% and 10% are selected, which are also used in previous studies [ 40 , 41 , 42 ]. To ensure the concentration of the sodium sulfate soaking solution remains unchanged, we replaced it every 30 times.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the high sulfate concentration in the water sample detection of the test tunnel, the experiment requires a strict sulfate concentration. Therefore, sodium sulfate immersion concentrations of 2% and 10% are selected, which are also used in previous studies [ 40 , 41 , 42 ]. To ensure the concentration of the sodium sulfate soaking solution remains unchanged, we replaced it every 30 times.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in the Table 7, the overall cracking load and instability load increase first and then decrease with the increase of dry-wet cycles, and the ratio of the two is 0.7 to 0.9. At the initial stage of corrosion, part of the sulfate radicals enters the concrete to form expansive products such as gypsum and ettringite, which fills the crevices of the concrete, increases the density, improves the crack resistance and limits cracking performance of concrete, and therefore increases the fracture toughness [26,27]. With the increase of corrosion age, the volume of crystallization products expands and exceeds the bearing capacity of the pores, resulting in a large number of micro-cracks, and these micro-cracks form new channels, which accelerate the corrosion rate of sulfate [28].…”
Section: Fracture Toughness Of Modified Concretementioning
confidence: 99%
“…Experimental results presented by Liu et al [14] showed that following 80 CWD cycles of a sulphate attack, the compressive strength of ordinary concrete increased by 9.1 and 6.1% (subject to the water-cement ratio), while in the succeeding 120 CWD cycles, compressive strength decreased by 15.6 and 11.3%, respectively. Concrete soaking accelerated the corrosion caused by cyclic wetting and drying [14,37].…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature provides a number of studies on factors having an impact on concrete durability, including physical salt attack (PSA) [3][4][5][6][7][8][9][10][11][12][13], cyclic wetting and drying (CWD) [14][15][16], the water-cement ratio of the initial concrete mix [14,[17][18][19], chemical admixtures [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation